Investigation of Each Society for Fertility Preservation in Asia - Harzif, Achmad Kemal; Santawi, Victor Prana Andika; Maidarti, Mila; Wiweko, Budi (Frontiers in Endocrinology, 2019)
Fertility preservation (FP) remains a future direction for reproductive medicine. FP development is needed to keep up with advancements in other areas of medicine, such as cancer research that has successfully prolonged patients’ survival. The demand for optimum FP is sought by both patients and practitioners alike. The American Society of Clinical Oncology has published and updated several FP guidelines. However, these guidelines need to be optimized for each country due to the nature of FP that interacts with the local policy, social decorum, and economic factors. Furthermore, the availability and success rate for each procedure might differ since there is a requirement for advanced and innovative technologies involved in FP. These guidelines should ideally be supported by the FP society to overcome unique barriers that may arise in each country. Here we try to illustrate the most recent update on the condition of FP practice in several countries in Asia. This hopefully will encourage future FP development and might become a useful reference for other countries, especially in Asia.